Lorentz violation, Bhabha scattering and finite temperature (e-Boletim da Física, 2019)
In this paper an introduction to Lorentz violation has been done. Corrections due to Lorentz violation for the cross section of the Bhabha scattering has been calculated at zero and finite temperature. The finite temperature corrections are calculated using the Thermo Field Dynamics(TFD) formalism.